ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INFLASI DI INDONESIA MENGGUNAKAN METODE OLS - Prayogi, Agung (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2022)
The reason for this research is to determine the effect of the money supply, GDP growth, and interest rates on the inflation rate during the period 1986-2019 in Indonesia. The research method used in the analysis uses Ordinary Least Square (OLS) or multiple linear regression. The findings of the analysis of research results show that there is a positive and significant effect on the money supply on inflation in Indonesia in the long term. GDP growth shows a negative and significant effect on inflation in Indonesia. Meanwhile, interest rates have a negative effect on inflation in Indonesia but are not significant. However, simultaneously or simultaneously the money supply, GDP growth, and interest rates have an influence on the inflation rate in Indonesia.